Lean Manufacturing System at Rainbow Enterprise - Mohd Alwi, Norhayati; Zainal Abidin, Nor Hafizah; Mokhtar, Norsyahida (IIUM Journal of Case Studies in Management, 2020)
Mr. Johan was wondering how long his business could sustain. His company, Rainbow Enterprise was suffering from some internal problems. Being an owner-manager, Mr. Johan had to shoulder the challenges alone. Fortunately, in November 2017, he was introduced to Mr. Syakir, a consultant funded by Malaysian Productivity Centre. Between February and October 2018, the consultant provided some coaching and training to Rainbow Enterprise. In just a few months, the lean manufacturing system was introduced. Rainbow Enterprise invested some capital on changing the factory layout, improving the inventory management system and introducing proper planning and control system. Despite the changes, there were still issues that worth to be highlighted. Firstly, the company had production workers who were reluctant to change their attitude towards the new system. Secondly, due to the capacity issue on the management side, the 5S system was temporarily put on hold. Thirdly, it was still too soon to translate the results of the changes into monetary terms. By the end of 2018, Mr. Johan was still in doubt of the actual improvements that the consultant and the lean manufacturing system had offered him. How could Mr. Johan sustain his business? How could he progress further? Why were production workers reluctant to change? Were there hopes for future growth?